COMPLEX ASSESSMENT OF THE INFLUENCE OF EXTERNAL ENVIRONMENTAL FACTORS ON THE IMPLEMENTATION OF QUALITY MANAGEMENT SYSTEMS IN UZBEKISTAN AGROINDUSTRIAL CHAINS (Marketing Journal, 2025)
This article examines the necessity of implementing quality management systems in Uzbekistan’s agro -industrial chains based on international experience, scientific approaches, and the PESTEL analysis model. It analyzes how developed countries such as the E uropean Union, the United States, and Japan have enhanced the sustainability and export potential of agro -industry through standards like ISO 9001, GlobalG.A.P., and HACCP. The scientific foundations developed by global scholars, particularly the integrati on of digital transformation into quality monitoring, environmental control, and traceability technologies, are argued to be essential for Uzbekistan as well. The study develops indices based on PESTEL components and determines their integration through ex pert evaluations. The results indicate that technological and political infrastructure is relatively well developed, while the legal and social environment remains weak. Thus, the article provides scientific justification for introducing quality management systems in Uzbekistan’s agrarian sector in harmony with international standards and digital technologies.
Keywords: quality management; agro -industrial chain; PESTEL analysis; GlobalG.A.P; ISO 9001; HACCP; digital technologies; environmental sustainability; expert evaluation; traceability system; digital transformation; legal environment; economic efficiency; Uzbekist an’s agrarian sector; indexing methodology